Statistical Analysis from Quantifying susceptibility of marine invertebrate biocomposites to dissolution in reduced pH - Matthew Chadwick; Elizabeth M. Harper; Anaëlle Lemasson; John I. Spicer; Lloyd S. Peck (2019)
Two-way ANOVA values comparing thickness loss under the two pH treatments (ambient and reduced) for each microstructure. Multiple regression analysis values for every possible grouping of the measured microstructural characteristics. The regression values are calculated for all microstructures and just the bivalve microstructures.